Decellularized Tooth Bud Scaffolds for Tooth Regeneration. (May 2017) - Zhang, W.; Vazquez, B.; Oreadi, D.; Yelick, P.C.
Whole tooth regeneration approaches currently are limited by our inability to bioengineer full-sized, living replacement teeth. Recently, decellularized organ scaffolds have shown promise for applications in regenerative medicine by providing a natural extracellular matrix environment that promotes cell attachment and tissue-specific differentiation leading to full-sized organ regeneration. We hypothesize that decellularized tooth buds (dTBs) created from unerupted porcine tooth buds (TBs) can be used to guide reseeded dental cell differentiation to form whole bioengineered teeth, thereby providing a potential off-the-shelf scaffold for whole tooth regeneration. Porcine TBs were harvested from discarded 6-mo-old pig jaws, and decellularized by successive sodium dodecyl sulfate/Triton-X cycles. Four types of replicate implants were used in this study: 1) acellular dTBs; 2) recellularized dTBs seeded with porcine dental epithelial cells, human dental pulp cells, and human umbilical vein endothelial cells (recell-dTBs); 3) dTBs seeded with bone morphogenetic protein (BMP)-2 (dTB-BMPs); and 4) freshly isolated nondecellularized natural TBs (nTBs). Replicate samples were implanted into the mandibles of host Yucatan mini-pigs and grown for 3 or 6 mo. Harvested mandibles with implanted TB constructs were fixed in formalin, decalcified, embedded in paraffin, sectioned, and analyzed via histological methods. Micro-computed tomography (CT) analysis was performed on harvested 6-mo samples prior to decalcification. All harvested constructs exhibited a high degree of cellularity. Significant production of organized dentin and enamel-like tissues was observed in dTB-recell and nTB implants, but not in dTB or dTB-BMP implants. Micro-CT analyses of 6-mo implants showed the formation of organized, bioengineered teeth of comparable size to natural teeth. To our knowledge, these results are the first to describe the potential use of dTBs for functional whole tooth regeneration.